EUROPEAN AND WORLD PRACTICES OF FORMING A COMPREHENSIVE HUMANITARIAN SPACE - Petro Opanashchuk (Публічне управління та регіональний розвиток, 2025)
The article examines the formation of a comprehensive humanitarian space in modern conditions. It is determined that it is gaining strategic importance, as it encompasses the integration of policies in the spheres of culture, education, preservation of cultural heritage, formation of national identity, as well as the regulation of interethnic and interfaith relations. The article analyzes the main theoretical approaches to humanitarian policy, presented in the works of Pierre Bourdieu, Stuart Hall, Arjun Appadurai and John Tomlinson. Particular attention is paid to the analysis of cultural practices as a mechanism of social mobilization and a means of ensuring social integration. The international experience of forming a humanitarian space is studied using the example of Great Britain, France, Germany, Italy, Spain, the USA, Canada, Japan and South Korea. Key trends and challenges in the development of humanitarian policy in the context of globalization are identified, in particular the impact of digitalization, which opens up new opportunities for intercultural communication, interactive knowledge exchange and the formation of a common information space. Special attention is paid to the Ukrainian context of the formation of the humanitarian space. The processes of adaptation of European and world experience are analyzed, in particular in the field of state regulation of cultural policy and mechanisms for preserving national identity. Key challenges are identified: uneven distribution of funding for cultural initiatives, language barriers, digital inequality, problems of intercultural interaction and information security. The results of the study can be used to develop public administration strategies aimed at preserving cultural heritage, developing educational institutions, strengthening national identity, and ensuring information security in the context of digital transformation and global challenges.